2020
DOI: 10.1371/journal.pone.0232967
|View full text |Cite
|
Sign up to set email alerts
|

Staurosporine and NEM mainly impair WNK-SPAK/OSR1 mediated phosphorylation of KCC2 and NKCC1

Abstract: The pivotal role of KCC2 and NKCC1 in development and maintenance of fast inhibitory neurotransmission and their implication in severe human diseases arouse interest in posttranscriptional regulatory mechanisms such as (de)phosphorylation. Staurosporine (broad kinase inhibitor) and N-ethylmalemide (NEM) that modulate kinase and phosphatase activities enhance KCC2 and decrease NKCC1 activity. Here, we investigated the regulatory mechanism for this reciprocal regulation by mass spectrometry and immunoblot analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 119 publications
(225 reference statements)
1
28
0
Order By: Relevance
“…We then asked if the altered DFGABA values could be due to alteration in the expression of the The quantitative western blot analysis of the total KCC2 protein expression in hippocampi of P7 mice did not reveal statistically significant difference of the amount of KCC2 between WT and Magel2 KO animals ( Figure 9 A-B). The ion-transport activity of KCC2 and its stability at the cellular plasma membrane also strongly depend on posttranslational modifications of multiple phosphorylation sites (50). We therefore applied in a next step phospho-site-specific antibodies, as they were previously shown to quantitatively monitor changes in KCC2…”
Section: Post-translational Changes In Cation-chloride Co-transportermentioning
confidence: 99%
“…We then asked if the altered DFGABA values could be due to alteration in the expression of the The quantitative western blot analysis of the total KCC2 protein expression in hippocampi of P7 mice did not reveal statistically significant difference of the amount of KCC2 between WT and Magel2 KO animals ( Figure 9 A-B). The ion-transport activity of KCC2 and its stability at the cellular plasma membrane also strongly depend on posttranslational modifications of multiple phosphorylation sites (50). We therefore applied in a next step phospho-site-specific antibodies, as they were previously shown to quantitatively monitor changes in KCC2…”
Section: Post-translational Changes In Cation-chloride Co-transportermentioning
confidence: 99%
“…Lee and team reported that phosphorylation of KCC2 specific residue, Ser940, by protein kinase C (PKC) have been shown to activate KCC2, an isoform exclusively expressed in the nervous system. However, the phosphorylation of highly conserved threonine residues in all KCCs are all associated with inactivation [26,[30][31][32]. Thus the phosphorylation-mediated-activation of KCC2 may be an adaptive mechanism to assist with KCC2 functions in the nervous system [31,33,34].…”
Section: Functional Regulation Of the Cation Chloride Cotransporter Fmentioning
confidence: 99%
“…Lee and team reported that phosphorylation of KCC2 specific residue, Ser940, by protein kinase C (PKC) has been shown to activate KCC2, an isoform exclusively expressed in the nervous system. However, the phosphorylation of highly conserved threonine residues in all KCCs is ubiquitously associated with inactivation [ 33 , 37 , 38 , 39 ]. Thus, the phosphorylation-mediated-activation of KCC2 may be an adaptive mechanism to assist with KCC2 functions in the nervous system [ 38 , 40 , 41 ].…”
Section: Functional Regulation Of the Cation Chloride Cotransportementioning
confidence: 99%